O processo político de criaç\~ao da moeda comun europeia - Wagner Sousa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This work is about the question of Franco-German relations and the creation of the European common currency. For this purpose the analysis was made with the perspective of international political economy. Between the meetings of European leaders in the Dutch cities of Hague and Maastricht, among 1969 and 1992 the European monetary integration had developed with the Werner Plan, the "Snake", the European monetary system and finally the decision for the creation of a common currency, after German reunification. Geopolitics and geo-economic concerns influenced this question, materialized in a floating rate regime with liberalization of capital movements add relations between superpowers in the Cold War with your tensions and strains. The objective too is to demonstrate the fragile basis when the project of the common currency is supported.
Keywords: F01; F02; 330; European Union; Franco-German relations; common currency; regional integration